Evaluasi Website Hypermart.co.id dan Transmartdelivery.com Dengan Menggunakan Metode Webuse - Handoko Handoko; Joosten Joosten (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2023)
During the COVID-19 pandemic, some people are spending more time at home. So, many people prefer to shop online, especially to buy basic needs. This is what causes the trend of online shopping to continue to increase rapidly during the pandemic. This certainly has an impact on the number of visitors to e-commerce websites, including hypermart.co.id and transmartdelivery.com, which should increase during this pandemic. So that this becomes a problem, it is necessary to use usability analysis to improve services so that customers of both websites get the best online shopping experience by utilizing the Webuse method. This method consists of 4 usability variables, namely Content Organization and Readability, Link and Navigation, User Interface and Design, and Performance and Effective. This study uses data from 100 respondents according to the research criteria. The results showed that the overall usability of hypermart.co.id and transmartdelivery.com e-commerce websites was at a good level, with 3.14 usability points on hypermart.co.id and 3.13 on transmartdelivery.com which means hypermart.co.id and transmartdelivery.com have been able to meet user satisfaction in terms of usability, including content, navigation, interface and performance.